Increase in IL-15 levels in patients with alopecia areata - Madras, Dominika Katarzyna; Rocka, Agata; Piędel, Faustyna; Psiuk, Dominika; Nowak, Emilia (Journal of Education, Health and Sport, 2020)
Introduction and purpose: Alopecia areata (AA) is a condition that causes non-scarring hair loss (often with acute onset). Alopecia areata in the population occurs in 0.1-0.2% of people, with a similar frequency in men and women. Alopecia areata is an example of an autoimmune disease of the hair follicle. Hair loss in alopecia areata is caused by lymphocytic infiltration around the hair follicle and IFN-γ. IgG antibodies against hair follicle cells are also found in people suffering from alopecia areata. Recent studies have shown a significant increase in IL-15 in AA. The aim of the study was to review the current knowledge on the use of IL-15 in the treatment of alopecia areata. A brief description of the state of knowledge: Interleukin-15 (IL-15) is a pleiotropic cytokine that exhibits multidirectional biological effects on various cell types. It affects the functions of the immune system, both innate and acquired, and therefore plays an important role in inflammation and during the immune response to infections and infestations. In the AA mouse model, antibody-mediated blockade of IFN-γ, interleukin-2 (IL-2), or interleukin-15 receptor β (IL-15Rβ) prevented disease progression by minimizing the accumulation of CD8 (+) NKG2D (+) T cells in the skin and reducing the cutaneous IFN response. The concentration of IL-15 in patients with alopecia areata was significantly higher than in the control group. Moreover, the concentration of IL-15 increased in direct proportion to the area of alopecia, the highest value in patients with total alopecia. For this reason, it is important to search for new medical treatments that will enable patients to stay physically healthy, and what is equally important, to remain mental health. Conclusions: In addition, studies have shown an increase in IL-15 levels in patients with alopecia areata, which correlated with the duration of the disease. However, too few studies conducted so far do not allow conclusions to be drawn regarding the use of IL-15 as a therapeutic point.